2011
DOI: 10.18632/oncotarget.361
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral activity of allosteric inhibitors of protein kinase CK2

Abstract: IntroductionDue to its physiological role into promoting cell survival and its dysregulation in most cancer cells, protein kinase CK2 is a relevant physiopathological target for development of chemical inhibitors. We report the discovery of azonaphthalene derivatives, as a new family of highly specific CK2 inhibitors. First, we demonstrated that CK2 inhibition (IC50= 0.4 μM) was highly specific, reversible and non ATP-competitive. Small Angle X-ray Scattering experiments showed that this inhibition was due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 52 publications
1
36
0
3
Order By: Relevance
“…CK2 is being regarded as an emerging anti-tumor therapeutic target [18], and CK2 inhibition suppresses prosurvival signaling pathways and growth of glioblastoma [19]. Since metabolism, senescence and survival of cancer cells are intricately connected, and as possible initiation of clinical trials using CK2 antagonists in chronic lymphocytic leukemia holds promise [20]; we studied the effect of CK2 inhibition on the metabolic adaptation in glioma cells and its consequences on the survival of these cells, in both in vitro and in vivo mouse xenograft model of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…CK2 is being regarded as an emerging anti-tumor therapeutic target [18], and CK2 inhibition suppresses prosurvival signaling pathways and growth of glioblastoma [19]. Since metabolism, senescence and survival of cancer cells are intricately connected, and as possible initiation of clinical trials using CK2 antagonists in chronic lymphocytic leukemia holds promise [20]; we studied the effect of CK2 inhibition on the metabolic adaptation in glioma cells and its consequences on the survival of these cells, in both in vitro and in vivo mouse xenograft model of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…La faculté de bloquer simultanément CK2 et PIM dans ce type de cancers est donc particulièrement intéressante [6]. Des dérivés des azonaphatalènes, qui induisent un changement de conformation de type allostérique après leur fixation sur CK2, se montrent efficaces dans un modèle de xénogreffes de glioblastome [4]. Les polyoxométalates (POM), quant à eux, sont des agrégats nanométriques anioniques de métaux de transition (vanadium, molybdène, tungstène).…”
Section: Start-up Et/ou Transfert Vers Un Partenaire Industrielunclassified
“…TAMIS évolue continuellement, notamment pour l'inté-gration de méthodes d'analyses statistiques innovantes dédiées à l'analyse des résultats de HTS et HCS ; ces méthodes ont été développées en collaboration avec le Pr R. Nadon de l'Université de Montréal [32][33][34][35]. 4 Groupe informatique pour le sud-est.…”
Section: Revuesunclassified
See 1 more Smart Citation
“…It has been reported that deregulation of CK2 activity could be linked to the development of human cancers [18], and that its up-regulation has been described in glioblastomas [19]. Moreover, CK2 inhibition has been shown to have anti-tumor effect in human-glioblastoma xenografts [19,20]. In this study, we used an siRNA targeting the beta subunit of CK2 (CK2β), previously reported to inhibit at least 70% of CK2β activity [21].…”
Section: Introductionmentioning
confidence: 99%